Banking and Regulation in Emerging Markets : The Role of External Discipline - Vives, Xavier (Oxford University Press on behalf of the World Bank, 2013)
This article reviews the main issues of regulating and supervising banks in emerging markets with a view toward evaluating the long-run options. Particular attention is paid to Latin America and East Asia. These economies face a severe policy commitment problem that leads to excessive bailouts and potential devaluation of claims of foreign investors. This exacerbates moral hazard and makes a case for importing external discipline (for example, acquiring foreign short-term debt). However, external discipline may come at the cost of excessive liquidation of entrepreneurial projects. The article reviews the tradeoffs imposed by external discipline and examines various arrangements, such as narrow banking, foreign banks and foreign regulation, and the potential role for an international agency or international lender of last resort.